Lymphatic mapping with SPECT‐CT for evaluation of contralateral drainage in lateralized oropharyngeal cancers using an awake injection technique. Issue 3 (28th November 2019) - Thomas, Carissa M.; Khan, Mohemmed N.; Mohan, Ravi; Hendler, Aaron; Hosni, Ali; Chepeha, Douglas B.; Goldstein, David P.; Cooper, Richard M; de Almeida, John R.
Abstract: Background: Risk of contralateral nodal metastases in oropharyngeal squamous cell carcinoma (OPSCC) is currently based on clinical risk factors. We propose lymphatic mapping with single photon emission computed tomography (SPECT‐CT) for tumor‐specific delineation of lymphatic drainage to guide treatment. Methods: Retrospective review of lymphatic drainage patterns in cT1‐2 OPSCC and contralateral cN0 neck with a nonoperative, awake injection of 99 m‐Tc sulfur colloid and SPECT‐CT. Results: Ten patients were reviewed. Primary sites included tonsil (n = 8, 80%) and tongue base (n = 2, 20%). All patients tolerated awake injections with no complications. Nine patients (90%) demonstrated satisfactory migration of radiotracer to neck node(s) with seven (78%) to the ipsilateral lateral neck, one (11%) to the ipsilateral lateral neck and retropharynx, and one (11%) to bilateral lateral neck nodes. Conclusions: Characterization of lymphatic drainage in OPSCC is feasible using a nonoperative injection technique and SPECT‐CT. Drainage to the contralateral neck is rare, warranting further study to tailor treatment appropriately.